2022
DOI: 10.1021/acsami.2c05354
|View full text |Cite
|
Sign up to set email alerts
|

Novel YOF-Based Theranostic Agents with a Cascade Effect for NIR-II Fluorescence Imaging and Synergistic Starvation/Photodynamic Therapy of Orthotopic Gliomas

Abstract: Accurate diagnosis and highly effective treatment of glioblastoma are still challenges in clinic. Near-infrared (NIR) light triggered fluorescence imaging and photodynamic therapy (PDT) showed the potential for theranostics of glioblastoma, but the presence of blood-brain barrier (BBB) and hypoxia limited treatment effect. Herein, the novel theranostic nanoagents with YOF:Nd3+ as core, MnO2 as shell, and further loading photosensitizer (indocyanine green, ICG) and glucose oxidase (GOx) were successfully constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…developed the novel theranostic nanoagents (YMIGL) composed of YOF: Nd 3+ as NIR fluorescence imaging probes, MnO 2 as oxygen generator, ICG as photosensitizer, glucose oxidase (GOx) as energy‐consuming substance, and lactoferrin as targeting molecule for orthotopic glioblastoma therapy. [ 97 ] When YMIGL was endocytosed by glioblastoma cells, the GOx consumed glucose and produced gluconic acid and H 2 O 2 , which could cause a significant upregulation of H 2 O 2 levels and acidity in the environment, leading to the generation of oxygen via degrading MnO 2 shell. ICG was activated by 808 nm laser to generate amount of ROS, which was greatly enhanced by oxygen generation.…”
Section: Nir Light Responsive Materials For Effective Therapy Of Brai...mentioning
confidence: 99%
“…developed the novel theranostic nanoagents (YMIGL) composed of YOF: Nd 3+ as NIR fluorescence imaging probes, MnO 2 as oxygen generator, ICG as photosensitizer, glucose oxidase (GOx) as energy‐consuming substance, and lactoferrin as targeting molecule for orthotopic glioblastoma therapy. [ 97 ] When YMIGL was endocytosed by glioblastoma cells, the GOx consumed glucose and produced gluconic acid and H 2 O 2 , which could cause a significant upregulation of H 2 O 2 levels and acidity in the environment, leading to the generation of oxygen via degrading MnO 2 shell. ICG was activated by 808 nm laser to generate amount of ROS, which was greatly enhanced by oxygen generation.…”
Section: Nir Light Responsive Materials For Effective Therapy Of Brai...mentioning
confidence: 99%
“…In 2022, Lv et al designed diagnostic and theranostic nanoplatforms, which consisted of YOF:Nd 3+ with NIR-II emission as the core, MnO 2 as shell, photosensitizer ICG, glucose oxidase (GOx) and lactoferrin with BBB penetration and targeted capabilities (YOF:Nd 3+ @MnO2-ICG-GOx-LF, YMIGL) for NIR II-guided synergistic starvation, and PDT therapy of orthotopic GBM. 87 GOx can consume glucose to produce H 2 O 2 and gluconic acid to achieve starvation treatment at the tumor sites, 88 and the O 2 concentration in situ was enhanced through the cascade reaction between GOx and MnO 2 to improve therapeutic efficiency of PDT. NIR-II fluorescence imaging of orthotopic GBM revealed that YMIGL can effectively penetrate the BBB and accumulate in the tumor region compared to YMIG without targeted peptide.…”
Section: Treatment Of Gbm By Pdtmentioning
confidence: 99%
“…However, several challenges remain, such as the accurate detection of cancer metastasis at the preoperative or even intraoperative stage and improvement of the spatial and temporal resolution. Although the NIR-II spectra is available for through-skull penetration in vivo , the poor capacity of NIR-II nano-systems for crossing the BBB significantly limits the imaging contrast and therapeutic efficacy for glioma detection ( Zhang H. et al, 2022 ; Lv et al, 2022b ; Men et al, 2022 ). By equipping fluorescent probes with targeted delivery systems, the accumulation of NIR agents at glioma tumor sites can be improved.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%